19F MRI Tracer Preserves in Vitro and in Vivo Properties of Hematopoietic Stem Cells. Issue 1 (January 2013) - Helfer, Brooke M.; Balducci, Anthony; Sadeghi, Zhina; O'hanlon, Charles; Hijaz, Adonis; Flask, Chris A.; Wesa, Amy
Hematopoietic stem cells (HSCs) have numerous therapeutic applications including immune reconstitution, enzyme replacement, regenerative medicine, and immunomodulation. The trafficking and persistence of these cells after administration is a fundamental question for future therapeutic applications of HSCs. Here, we describe the safe and efficacious labeling of human CD34 + HSCs with a novel, self-delivering perfluorocarbon 19 F magnetic resonance imaging (MRI) tracer, which has recently been authorized for use in a clinical trial to track therapeutic cells. While various imaging contrast agents have been used to track cellular therapeutics, the impact of this MRI tracer on HSC function has not previously been studied. Both human CD34 + and murine bone marrow (BM) HSCs were effectively labeled with the MRI tracer, with only a slight reduction in viability, relative to mock-labeled cells. In a pilot study, 19 F MRI enabled the rapid evaluation of HSC delivery/retention following administration into a rat thigh muscle, revealing the dispersal of HSCs after injection, but not after surgical implantation. To investigate effects on cell functionality, labeled and unlabeled human HSCs were tested in in vitro colony forming unit (CFU) assays, which resulted in equal numbers of total CFU as well as individual CFU types, indicating that labeling did not alter multipotency. Cobblestone assay forming cell precursor frequency was also unaffected, providing additional evidence that stem cell function was preserved after labeling. In vivo tests of multipotency and reconstitution studies in mice with murine BM containing labeled HSCs resulted in normal development of CFU in the spleen, compared to unlabeled cells, and reconstitution of both lymphoid and myeloid compartments. The lack of interference in these complex biological processes provides strong evidence that the function and therapeutic potential of the HSCs are likely maintained after labeling. These data support the safety and efficacy of the MRI tracer for clinical tracking of human stem cells.